PEMENUHAN KESEJAHTERAAN ANAK NELAYAN DALAM BIDANG PENDIDIKAN DI KELURAHAN JAMBULA: Fulfilling The Welfare Of Fisherman Children In The Education Field In Jambula District - M Ilmar Fahrezy; Wahyuni Retnowulandari (Faculty of Law, Universitas Trisakti, 2025)
Children have the right to welfare, care, upbringing and guidance based on affection in their families to grow and develop naturally, especially in terms of education, but in fact the fulfillment of education has not been met evenly throughout Indonesia as mandated by law. Therefore, the main problems of this research are: 1) How are the conditions of the growth and development of fishermen's children in the field of education in Jambula Village, Ternate City? 2) Are child welfare efforts in Ternate City in accordance with those stipulated in the Child Welfare Law? To answer these problems, this study uses a socio-relief research method, using secondary data sources and primary data, analyzed qualitatively and concluded inductively, descriptively. The results of the study stated that in Jambula Village, the implementation of fishermen's children's education has not been met due to economic problems. There are still children who are taken by their parents to sea and the government's efforts to distribute School Operational Assistance (BOS), thus ensuring that educational problems can be resolved immediately.